2008
DOI: 10.1080/10407780801960241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat and Mass Transfer Through Diffusive Walls on Three-Dimensional Double-Diffusive Natural Convection

Abstract: A three-dimensional numerical study using vorticity-vector potential formulations based on the finite-volume method has been performed to investigate double-diffusive convection in a stack of cubic enclosures submitted to horizontal gradients of temperature and concentration. The flow is driven by conditions of constant temperature and concentration imposed along the two vertical side walls of each cubic enclosure, while the horizontal walls are diffusive in heat and mass. This numerical study is conducted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…They indicated that the doublediffusive flow in enclosures was strictly three-dimensional for a certain range of Rayleigh numbers, Lewis numbers and buoyancy ratios respectively. The same configuration was studied by Abidi et al [14] but with heat and mass diffusive horizontal walls. They mentioned that the effect of the heat and mass diffusive walls was found to reduce the transverse velocity for the thermal buoyancy-dominated regime and to increase it considerably for the compositional buoyancydominated regime.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…They indicated that the doublediffusive flow in enclosures was strictly three-dimensional for a certain range of Rayleigh numbers, Lewis numbers and buoyancy ratios respectively. The same configuration was studied by Abidi et al [14] but with heat and mass diffusive horizontal walls. They mentioned that the effect of the heat and mass diffusive walls was found to reduce the transverse velocity for the thermal buoyancy-dominated regime and to increase it considerably for the compositional buoyancydominated regime.…”
Section: Introductionmentioning
confidence: 75%
“…This convection was largely studied for aiding or opposed temperature and concentration gradients. Studies on this subject can be found in several publications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It was noted that, for a buoyancy number near the unity, an oscillatory flow takes place, caused by the interaction between thermal and compositional cells.…”
Section: Introductionmentioning
confidence: 98%
“…They mentioned that the 3D character is dominant for a certain range of parameters. Abidi et al (2008) studied the same configuration with heat and mass diffusive horizontal walls. The results show that there is a great difference between the cases of the compositionally dominated flow and thermally dominated one.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid in the diffusive interface is initially constant, but the interface changes into a new cell under a fixed condition. A 3D numerical analysis by using vorticity-vector potential formulations with finite-volume method has been performed to study the double-diffusive convection in a stack of cubic enclosures by Abidi et al (2008). Their findings showed that the effect of heat and mass diffusive walls differs between the case of thermally dominated flow and the compositionally dominated one.…”
Section: Introductionmentioning
confidence: 99%